Sexual offenders treatment models - Luković Milica; Petrović Vera (Specijalna Edukacija i Rehabilitacija, 2017)
Sexual violence is a complex social and criminological problem that attracts a lot of attention not only of scientists, but also of the general public and requires immediate reaction of the society. The worldwide applied programs of re-socialization of sexual offenders are based on cognitive-behavioral therapy, deviant fantasies control and preventive strategies and new life goals construction. The therapies aim to develop empathy with the victim, change the way of thinking and change behavior. Among the leading models successfully applied in penological treatment of sexual offenders, there are models based on cognitive-behavioral therapy, such as Relapse Prevention Model, RNR model, Self-Regulation Model and Good Lives Model.